2023
DOI: 10.12804/revistas.urosario.edu.co/empresa/a.12143
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de los Objetivos de Desarrollo Sostenible priorizados por las compañías latinoamericanas

Abstract: Los Objetivos de Desarrollo Sostenible (ODS) implementados como una meta de sostenibilidad a nivel global por la Asamblea General de las Naciones Unidas plantean como propósito alcanzar el bienestar humano a través de la protección del medio ambiente, la igualdad, la reducción de la pobreza, la educación y el diseño de ciudades y pueblos. Con este artículo se pretende caracterizar las prácticas de revelación de dichos objetivos en Latinoamérica. Para este propósito se desarrolló un modelo de análisis de conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These findings provide theoretical contributions and have practical implications. From a theoretical perspective, this study contributes to the knowledge about a novel and incipient phenomenon, the B Corp movement, responding to the call of various authors to further research this topic [17] and especially about the way in which B Corporations contribute to SDGs [2]. In this regard, the present study expands the limited research on this topic [14,27], revealing the concrete contributions of B Corporations to SDGs through their practices by providing solutions to environmental and social problems.…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 58%
See 2 more Smart Citations
“…These findings provide theoretical contributions and have practical implications. From a theoretical perspective, this study contributes to the knowledge about a novel and incipient phenomenon, the B Corp movement, responding to the call of various authors to further research this topic [17] and especially about the way in which B Corporations contribute to SDGs [2]. In this regard, the present study expands the limited research on this topic [14,27], revealing the concrete contributions of B Corporations to SDGs through their practices by providing solutions to environmental and social problems.…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 58%
“…A study by Nicoló et al [22] showed that many of the world's leading companies that adopt integrated reporting address issues related to SDGs in such reports. Similarly, companies from countries of the Latin American Integrated Market mention SDGs in their integrated, combined, and sustainability reports [17]. Izzo et al [20] demonstrated that Italian companies mainly disclose SDGs in sustainability reports and non-financial statements.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the private sector in Latin America, the prioritisation of the SDGs is entirely voluntary. Thus, in many cases, small and medium-sized enterprises (SMEs) do not directly engage with the 2030 Agenda, and larger companies are the primary actors in this respect [ 32 ]. When these organisations prioritise the SDGs they wish to align with, this provides a structure for their business strategies, facilitating a clearer overview of resource allocation in the context of sustainability [ 33 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%